Phylogenic Relationship of Labridae Species Deduced from Comparative Dissection. Issue 5 (13th March 2013) - Mikami, Yoshikazu
ABSTRACT Labridae is a family of shallow‐water coastal fish that belong to the Labroidei suborder in the Perciformes order. There has however been little comparative dissection or phylogenetic research on this family, which resulted in confusion regarding species classification. Therefore morphological characters of 12 species of Labridae containing three subfamilies and seven genera were compared for the purpose of determining the characteristics of the subfamilies and genera of Labridae and deducing their phylogenic relationship. We compiled a phylogenetic tree by using the computer program PAUP 4.0b10 and a data set composed of 17 meristic and osteological characters. In our phylogenic tree, the two species of Bodianinae, three species of Cheilininae and seven species of Corinae each formed monophyletic groups, supporting the conventional classification by lateral line shape. Furthermore, the group of three species of Cheilininae and the group of two species of Bodianinae were shown to be more closely related, because they have several common morphological characteristics, such as neuroarticular processes and anterior teeth on premaxilla. Between seven species of Corinae, not only was the group of two species of Halichoeres more closely related to Coris dorsomacula, but also, this group of three species may be closely related to the three species of Thalassoma. Suezichthys gracilis was also found to have separated from the other Corinae species at the earliest stage. Anat Rec, 296:788–797, 2013. © 2013 Wiley Periodicals, Inc.